(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2004)
This paper examines traditional approaches to death, seeing them not merely as manifestations of ’death anxiety’, but as creative and holistic ways of understanding both life and death. I suggest that such approaches return us to think of the intrinsic connection of life and death, as well as shedding light on the meaning of a ’good death’, apart from any particularly religious or otherworldly emphases. While not exhaustive in any sense, I offer some considerations for the impact which these traditional approaches could have on our modern understanding of what it means to live and to die well.